KUALITAS ILUSTRASI BUKU TEKS TEMATIK TERPADU TEMA â€œKELUARGAKUâ€ JILID 1D TERBITAN ERLANGGA - Lusiatania Ayu; Noor Riyadhi (Politeknik Negeri Media Kreatif, 2014)
This research aims to examine the quality of the illustration image in an integrated thematic textbooks for the theme of